Refined Techniques for Enabling Long-Term Cryo-Repository Using Vitrification and Laser Warming - Chiahsin Lin; Wen-Chung Hsieh; Kanokpron Loeslakwiboon; Cheng-Liang Huang; Ting-Chun Chen; Sujune Tsai (Bioengineering, 2023)
Vitrification and ultrarapid laser warming are crucial for the cryopreservation of animal embryos, oocytes, and other cells of medicinal, genetic, and agricultural value. In the present study, we focused on alignment and bonding techniques for a special cryojig that combines a jig tool and jig holder into one piece. This novel cryojig was used to obtain a high laser accuracy of 95% and a successful rewarming rate of 62%. The experimental results indicated that our refined device improved laser accuracy in the warming process after long-term cryo-storage through vitrification. We anticipate that our findings will lead to cryobanking applications that use vitrification and laser nanowarming to preserve cells and tissues from a wide range of species.